2017
DOI: 10.1186/s12879-016-2149-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus strains from Rwandan blood donors are genetically similar and form one clade within subgenotype A1

Abstract: BackgroundRwanda is a central African country with about 12 million inhabitants. The 1994 genocide against the Tutsi destroyed much of the infrastructure, including the health system. Although this has improved significantly, many challenges remain to be addressed. In this study, the prevalence of serological markers of past and ongoing hepatitis B virus (HBV) infection and HBV vaccine related immunity was investigated in samples from blood donors from all regions of Rwanda.MethodsThe results from hepatitis B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 45 publications
(49 reference statements)
4
25
0
Order By: Relevance
“…Rwanda is probably located at the East of a demarcation zone dividing Africa in West and East zones where genotypes E and A1 predominate, respectively . This hypothesis is supported by our findings, by the paper published by Twagirumugabe et al, and by the fact that the only case of genotype E identified in our study was obtained from a 41‐year‐old woman newly established in Bukavu and who was originated from Kinshasa, a western town of the DRC.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Rwanda is probably located at the East of a demarcation zone dividing Africa in West and East zones where genotypes E and A1 predominate, respectively . This hypothesis is supported by our findings, by the paper published by Twagirumugabe et al, and by the fact that the only case of genotype E identified in our study was obtained from a 41‐year‐old woman newly established in Bukavu and who was originated from Kinshasa, a western town of the DRC.…”
Section: Discussionsupporting
confidence: 90%
“…In the Sub-Saharan Africa, genotype A is mainly found in the austral and southern part while genotype E is the major type observed in West Africa (Figure 1). 11,[12][13][14] Until now, only one study was performed in the DRC and only involving samples coming from the western part of the country. 12 Results of the present study are surprising in regard with the high diversity of genotypes found in the study conducted by Hübschen et al 19 Tanzania, and Kenya.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations